Kindness - Catalán, Brenda (CIEX JOURNAL, 2018)
Oxford Dictionary (2018) defines kindness as the quality of being friendly, generous, and considerate. A simple definition, nevertheless those three other words imply three more values that have a lot to do with treating others politely, being considerate, being aware of the ones in need and willing to help them at least in the most minimal way.